INCLUSIVE ISLAMIC EDUCATION: FOSTERING TOLERANCE IN GENERATION Z WITHIN A MULTICULTURAL SOCIETY - Hamzah, Muhamad; Nuruddin, Muhammad Mamduh; Budiman, Septian Arief (FAJAR Jurnal Pendidikan Islam, 2025)
This study aims to explore the role of inclusive Islamic education in fostering tolerance among Generation Z within a multicultural society. Generation Z, born and raised in the era of globalization and digitalization, faces complex challenges related to cultural, religious, and ideological diversity. Using a qualitative-descriptive approach through case studies in several junior and senior high schools, this research examines how curriculum design, teaching methods, and the application of moderate Islamic values are integrated into Islamic Religious Education classrooms. The findings reveal that an inclusive approach to Islamic education—emphasizing the values of rahmatan lil ‘alamin (mercy to all creation), respect for differences, and interfaith dialogue—plays a significant role in shaping tolerant, open-minded, and diversity-appreciating attitudes among students. The study recommends strengthening the role of teachers as dialogue facilitators, developing contextual learning materials, and promoting cross-cultural collaboration as effective strategies to nurture a harmonious and pluralistic society